Methyl modified hydrogel electrolyte, preparation method thereof and application of methyl modified hydrogel electrolyte in zinc battery

Through the preparation method of methyl modified hydrogel electrolyte, the problem of disordered growth and salting out of zinc dendrites in zinc batteries is solved, and the high cycle life and good electrochemical performance of zinc batteries are achieved.

CN119650892AActive Publication Date: 2025-03-18ZHENGZHOU UNIV

Patent Information

Application Number
CN202411923095.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18
Estimated Expiration
2044-12-25

Smart Images

  • Figure CN119650892A_ABST
    Figure CN119650892A_ABST
Patent Text Reader

Abstract

The invention discloses a methyl modified hydrogel electrolyte, a preparation method thereof and application of the methyl modified hydrogel electrolyte in a zinc battery, and belongs to the field of secondary batteries. The hydrogel electrolyte is composed of acrylamide, methyl cellulose and zinc sulfate. The preparation method comprises the following steps: adding methyl cellulose and acrylamide into a zinc sulfate solution, uniformly mixing, then adding a potassium persulfate initiator and a cross-linking agent N, N '-methylene bisacrylamide, finally putting into a double-layer glass plate, sealing, and carrying out thermal polymerization. The methyl cellulose has zinc affinity and can convert an acrylamide proton polymer into an aprotic polymer to weaken intermolecular hydrogen bonds, so that free hydrogen bond receptors are released to participate in cationic solvation. The solubilization and recrystallization strategy can effectively adjust the gel electrolyte environment, cut off hydrogen bonds formed by binding water donors and participate in electrolyte salt dissolution, so that the electrolyte concentration is increased, and salting-out of the electrolyte is inhibited. When the gel electrolyte is applied to the zinc battery, zinc ion migration can be accelerated, and excellent cycle performance under a low-temperature condition is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of novel battery energy storage, and in particular relates to a methyl-modified hydrogel electrolyte, a preparation method thereof and application in a zinc battery. Background Art

[0002] Aqueous zinc-ion batteries have broad application prospects in large-scale energy storage and flexible wearable electronics due to their high theoretical capacity, abundant material reserves and high safety. However, uncontrollable interfacial reactions (dendrites, hydrogen evolution, corrosion) seriously hinder the large-scale development of zinc batteries. Hydrogel electrolytes can improve the stability of the electrode-electrolyte interface, but gel electrolytes usually contain a large amount of free water, which cannot inhibit the disordered growth of zinc dendrites and complex interfacial reactions. In addition, reducing the water content of traditional hydrogel electrolytes will lead to a large amount of salt precipitation and a decrease in ionic conductivity, thereby limiting its electrochemical performance. Therefore, the development of high ionic conductivity and maximized salt concentration gel electrolytes is crucial for long-life zinc batteries.

[0003] At present, the research on hydrogel electrolytes mainly focuses on two aspects: improving mechanical strength and mechanical properties and improving ionic conductivity. In order to improve the mechanical properties and ionic conductivity of hydrogel electrolytes, people have made a lot of efforts and research, but there is still a large amount of free water in the gel electrolytes in these strategies, which cannot fundamentally solve the interface problem. Increasing the salt concentration can effectively protect the stability of the electrode-electrolyte interface. Therefore, in addition to providing a stable cross-linked network, the polymer in the ideal gel electrolyte should also promote salt dissolution by participating in cation solvation. However, the traditional gel electrolytes currently used in zinc batteries contain both hydrogen bond acceptors and donors, resulting in the formation of hydrogen bond networks within the polymer molecules. Therefore, the polymer in the gel electrolyte hardly participates in the dissolution of the electrolyte, which leads to severe salt precipitation in the gel electrolyte and an imbalance in the ratio of free water and bound water. Summary of the invention

[0004] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a methyl-modified hydrogel electrolyte, a preparation method thereof and an application in a zinc battery. When the methyl-modified hydrogel electrolyte of the present application is used in a zinc battery, the uniform deposition of zinc ions is regulated, the interface stability is enhanced, and the cycle life of the zinc battery is improved.

[0005] In order to solve the technical problem of the present invention, the technical solution adopted is: A method for preparing a methyl-modified hydrogel electrolyte, the process is as follows: 1) Dissolve acrylamide and methyl cellulose in a zinc sulfate aqueous solution at a mass ratio of (1-3):1 and stir for 5-10 hours to mix them evenly; 2) Add thermal initiator and crosslinking agent to the mixed solution of step 1) and stir for 5 to 10 minutes; 3) The mixed solution of step 2) is placed in a double-layer substrate, coated evenly and sealed, and thermally polymerized at 50-70° C. to obtain a methyl-modified hydrogel electrolyte.

[0006] Furthermore, the thermal initiator is potassium persulfate or ammonium persulfate, and the cross-linking agent is N,N'-methylenebisacrylamide; the amount of the thermal initiator added is 1-5% of the mass of acrylamide; the mass ratio of the thermal initiator to the cross-linking agent is (1-3):1.

[0007] Furthermore, the spacing between the double-layer substrates is 0.1~1 mm, and the thermal polymerization time is 2~4 hours.

[0008] Further, the concentration of the aqueous zinc sulfate solution is 1-5 mol / L, and the concentration of acrylamide in the acrylamide is 0.05-0.1 mg / mL.

[0009] The methyl-modified hydrogel electrolyte prepared by the above preparation method can effectively promote the dissolution of zinc sulfate electrolyte salt and avoid salting out and crystallization in the gel electrolyte. Compared with the traditional gel electrolyte not containing methyl cellulose, the gel electrolyte prepared by this strategy has good salt dissolution characteristics and electrochemical properties.

[0010] Furthermore, the methyl-modified hydrogel electrolyte is used in zinc batteries.

[0011] Furthermore, the zinc sheet is used as the negative electrode, the zinc vanadate positive electrode or the zinc sheet is used as the positive electrode, and the prepared methyl-modified hydrogel electrolyte is used as the battery separator and electrolyte to be assembled into a quasi-solid-state zinc battery.

[0012] Furthermore, the quasi-solid-state zinc battery is a zinc-vanadate full battery and a zinc-zinc symmetric battery.

[0013] Furthermore, the structure of the zinc-zinc symmetrical battery is: positive electrode shell, zinc sheet, methyl-modified gel electrolyte, zinc sheet, gasket, negative electrode shell; the structure of the zinc-zinc vanadate full battery is: positive electrode shell, zinc vanadate positive electrode, methyl-modified gel electrolyte, zinc sheet, gasket, negative electrode shell.

[0014] The preparation process of the zinc vanadate positive electrode is as follows: the vanadium pentoxide is dispersed in a mixture of water and acetone, zinc acetate is added and stirred to dissolve, and then the mixture is transferred to a sealed polytetrafluoroethylene container, kept at 200±10°C for 70-75 hours, centrifuged and washed with water, the solid is collected and dried (dried at 50-70°C for 20-24 hours) to obtain zinc vanadate, PVDF is added to NMP and stirred until completely dissolved, zinc vanadate and acetylene black are ground and poured into the NMP solution of PVDF and stirred for 10-15 hours, applied on the current collector with a scraper, and dried (dried at 70-90°C for 4-6 hours) to obtain a zinc vanadate positive electrode.

[0015] Furthermore, the molar ratio of vanadium pentoxide to zinc acetate is 2:(1-1.5), the volume ratio of water to acetone is (10-20):1, and the mass ratio of zinc vanadate powder, acetylene black and PVDF is (6-8):(1-3):1.

[0016] Furthermore, the current collector is titanium foil or carbon felt.

[0017] Furthermore, the concentration of vanadium pentoxide in the mixture of water and acetone is 10-50 mol / L.

[0018] The beneficial effects relative to the prior art are: First, the gel electrolyte structure is regulated to maximize the salt concentration and control salt precipitation. The gel electrolyte is prepared by using the interaction between methyl cellulose and acrylamide to achieve electrolyte salt dissolution and recrystallization. This strategy converts acrylamide proton polymers into non-proton polymers through methyl cellulose to weaken intermolecular hydrogen bonds. At the same time, it can effectively adjust the gel electrolyte environment, cut off the bound water molecule donors to form hydrogen bonds, and release free hydrogen bond acceptors to participate in Zn 2+ Solvation. Compared with traditional hydrogel electrolytes, methyl-modified hydrogel electrolytes can avoid salting out, maximize the salt concentration and retain its bound water activity to enhance ionic conductivity and mechanical properties.

[0019] Second, stabilize the electrode-electrolyte interface and improve the electrochemical performance of zinc batteries. The hydrogel electrolyte prepared by methyl solubilization and recrystallization strategy was applied to zinc batteries. At a current density of 0.5 mA cm -2 , surface capacity is 0.5 mAh cm -2 Under the conditions, the assembled zinc-zinc symmetrical battery can achieve a plating / stripping cycle life of more than 8,000 hours, far exceeding the battery assembled with traditional gel electrolyte and the aqueous liquid battery assembled with glass fiber diaphragm. At the same time, the gel electrolyte has a good low-temperature performance. In a -20°C environment, the assembled zinc-zinc symmetrical battery can achieve a cycle stability of more than 2,200 hours. The assembled zinc-vanadate full battery has a stable capacity after 400 cycles under 1C rate charge and discharge conditions, with almost no attenuation. Compared with other patents, this technology can achieve ultra-long cycle stability, and at the same time has good low-temperature antifreeze performance, and its lifespan far exceeds other patent methods.

[0020] Third, the methyl solubilization and recrystallization strategy is novel, simple to prepare, and widely used. First, acrylamide and methyl cellulose are dissolved in a 2 mol zinc sulfate aqueous solution at a mass ratio of 2:1 and stirred for 5 to 10 hours to mix them evenly; then a small amount of thermal initiator and cross-linking agent are added and stirred for 5 to 10 minutes; the mixed solution is placed in a double-layer glass plate, coated evenly and sealed, and thermally polymerized in a 60°C oven to obtain a methyl-modified hydrogel electrolyte. The methyl solubilization and recrystallization strategy helps to maximize the electrolyte concentration and maintain the bound water activity. At the same time, the method is simple to operate, and the film-forming technology has been applied on a large scale. Application to zinc batteries can greatly improve their cycle life, which provides new theoretical guidance for the application of flexible batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the preparation of gel electrolyte and the methyl dissolution recrystallization strategy; Figure 2 are SEM images of the surface morphology of the gel electrolytes of Comparative Example 1 and Example 1; Figure 3 1 is a ternary solubilization equilibrium diagram of the gel electrolyte of Comparative Example 1 and Example 1; Figure 4 This is a study diagram of the gel electrolyte dissolution process of Comparative Example 1 and Example 1; Figure 5 is the ionic conductivity of the gel electrolyte and the glass fiber separator of Comparative Example 1 and Example 1; Figure 6 The SEM images of zinc electrode morphology after cycling of zinc-zinc symmetric batteries in Comparative Example 2, Comparative Example 3 and Example 2; Figure 7 The XRD diagrams of the zinc-zinc symmetric batteries of Comparative Example 2, Comparative Example 3 and Example 2 after different cycles; Figure 8 The effects of gel electrolyte and glass fiber diaphragm electrode corrosion in Comparative Example 1 and Example 1 are shown; Fig. 9 It is a long cycle test curve of zinc-zinc symmetrical batteries of comparative example 2, comparative example 3 and embodiment 2 at 25°C; Fig.10 This is a long cycle test curve of zinc-zinc symmetrical batteries at -20°C for comparative example 2, comparative example 3 and embodiment 2; Fig.11 Comparison of long cycle test results of zinc-zinc symmetric batteries (Comparative Example 2, Comparative Example 3 and Example 2) using different diaphragm electrolytes; Fig.12 1 is a cycle curve diagram of zinc vanadate full battery at 25° C. for comparative example 4, comparative example 5 and embodiment 3; Fig.13 It is a cycle curve diagram of zinc vanadate full batteries of comparative example 4, comparative example 5 and embodiment 3 at -20°C. DETAILED DESCRIPTION

[0022] The present invention is further described below by comparative examples and embodiments in conjunction with the accompanying drawings.

[0023] Comparative Example 1 Preparation and structural characterization of traditional hydrogel electrolytes (AM).

[0024] Step 1, preparation of conventional hydrogel electrolyte First, 0.8 g of acrylamide was dissolved in 10 mL of a 2 mol / L zinc sulfate aqueous solution and stirred for 6 hours to mix evenly. Then, 10 mg of potassium persulfate and 5 mg of N,N'-methylenebisacrylamide were added and stirred for 10 minutes. The mixed solution was placed on a double-layer glass plate and coated evenly and sealed. The spacing between the double-layer glass plates was 0.4 mm (i.e., the coating thickness was 0.4 mm). The solution was thermally polymerized in an oven at 60°C for 2 hours to obtain a traditional hydrogel electrolyte (AM).

[0025] Step 3, Structural characterization of conventional hydrogel electrolytes The surface morphology was observed using Zeiss dual ion beam scanning electron microscope (SEM). Figure 2 Large-scale salt precipitation occurs on the surface of traditional hydrogel electrolytes, which indicates that the structure of traditional hydrogel electrolytes is unstable and the water evaporates quickly.

[0026] Comparative Example 2 Assembling Zn-Zn symmetric cells using hydrophilic glass fiber separators.

[0027] Step 1, zinc electrode preparation A 200 μm thick pure zinc foil (purchased from Sinopharm Chemical Reagent) was ultrasonically cleaned with ethanol (ultrasonic frequency 40 kHz, power 300 W, time 5 min). The zinc foil was cut into pieces with a diameter of 12 mm and an area of ​​about 1.13 cm using an electrode slicer. 2 The disc was cleaned again with ethanol by ultrasound (ultrasonic frequency 40 kHz, power 300 W, time 5 minutes), and then placed in a vacuum oven at 40°C for 1 hour.

[0028] Step 2, zinc symmetric battery assembly The zinc electrodes were assembled into a CR2025 model (battery diameter is 20.0mm, thickness is 2.5mm) symmetrical battery for cycle stability test. The battery components are the positive electrode shell, zinc sheet, diaphragm, zinc sheet, stainless steel gasket (diameter 16mm, thickness 1mm), and negative electrode shell, and the sealing pressure is about 50 kg per cubic centimeter. The battery needs to be left at room temperature for at least 2 hours before use. The diaphragm is glass fiber (produced by Whatman, diameter 110mm, thickness 260μm, cut into 19mm diameter discs for use). The electrolyte used is 2mol / L (or 2M) zinc sulfate solution, 100μL is added to each battery, and the electrolyte is added after the diaphragm is placed. The preparation method of 2M zinc sulfate electrolyte is to dissolve ZnSO4∙7H2O (analytical grade, purchased from Sinopharm Chemical Reagent) in pure water, and the mass ratio of the two is about 5.751:7.48.

[0029] Step 3, zinc symmetric battery test Symmetrical battery long cycle test is carried out in a constant temperature box, and the temperature of the constant temperature box is kept at 25℃ to eliminate the influence of ambient temperature. Battery test uses Wuhan Landian battery test system. Fig. 9 As shown, the test parameters are set to constant current discharge and constant current charge, and the current density based on the electrode area is 1mA / cm 2 , area capacity is 0.5mAh / cm 2 Under this test condition, the life of the symmetrical battery using the hydrophilic glass fiber separator is about 355 hours, which shows that the battery life using the hydrophilic glass fiber separator is shorter. 2 , area capacity is 0.5mAh / cm 2 Tests such as Fig.10 , 11 As shown, the symmetrical battery life is about 27 hours. In addition, under deep discharge conditions, such as Fig.11 As shown, at 0.5 mA / cm 2 、10mAh / cm 2 Under normal conditions (DOD=68.33%), the symmetrical battery life is 300 hours.

[0030] Step 4: Observation of dendrites on the surface of zinc symmetric battery The surface morphology of the zinc electrode after 355 hours of death was observed using a Zeiss focused dual ion beam scanning electron microscope (SEM). Figure 6 As shown, after a long period of zinc deposition and stripping, the electrode surface is covered with disordered and irregular dendrites, which is the main cause of battery short circuit.

[0031] Comparative Example 3 Assembling Zn-Zn symmetric batteries using conventional hydrogel electrolytes Step 1, preparation of conventional hydrogel electrolyte membrane Same as step 1 of comparative example 1.

[0032] Step 2, zinc electrode preparation Same as step 1 of comparative example 2.

[0033] Step 3, zinc symmetric battery assembly The zinc electrodes were assembled into a CR2025 model (battery diameter is 20.0mm, thickness is 2.5mm) symmetrical battery for cycle stability test. The battery components are the positive electrode shell, zinc sheet, traditional hydrogel electrolyte membrane, zinc sheet, stainless steel gasket (diameter 16mm, thickness 1mm), negative electrode shell, and the sealing pressure is about 50 kg per cubic centimeter. The battery needs to be left at room temperature for at least 2 hours before use.

[0034] Step 4, zinc symmetric battery test Symmetrical battery long cycle test is carried out in a constant temperature box, and the temperature of the constant temperature box is kept at 25℃ to eliminate the influence of ambient temperature. Battery test uses Wuhan Landian battery test system. Fig. 9 As shown, the test parameters are set to constant current discharge and constant current charge, and the current density based on the electrode area is 1mA / cm 2 , area capacity is 0.5 mAh / cm 2 Under this test condition, the life of the symmetrical battery using the traditional hydrogel electrolyte is about 226 hours, which shows that the battery life using the traditional hydrogel electrolyte is short. 2 , area capacity is 0.5 mAh / cm 2 Tests such as Fig.10 , 11 As shown, the symmetrical battery life is about 240 hours. In addition, under deep discharge conditions, such as Fig.11 As shown, at 0.5 mA / cm 2 、10mAh / cm 2 Under the same conditions (DOD=68.33%), the symmetrical battery life is 460 hours.

[0035] Step 5: Observation of dendrites on the surface of zinc symmetric battery The surface morphology of the zinc electrode after 226 hours of death was observed using a Zeiss focused dual ion beam scanning electron microscope (SEM). Figure 6 As shown, after a long period of zinc deposition and stripping, the electrode surface is densely deposited, but the dendrites grow irregularly, limiting the cycle life of the battery.

[0036] Comparative Example 4 Assembling zinc vanadate full battery using hydrophilic glass fiber separator Step 1, zinc electrode preparation Same as step 1 of comparative example 2.

[0037] Step 2, preparation of zinc vanadate positive electrode Disperse 2 mol of vanadium pentoxide in a mixture of 50 mL of water and acetone (the volume ratio of water to acetone is 15:1), add 1.3 mol of zinc acetate and stir to dissolve, transfer to a sealed polytetrafluoroethylene container, store at 200 ° C for 72 hours, add pure water and centrifuge three times, collect the precipitate, and dry at 60 ° C for 24 hours to obtain zinc vanadate. Add 3~4 mL of NMP and 100 mg of PVDF to a glass bottle and stir for 6 hours. Then add 200 mg of acetylene black and 700 mg of zinc vanadate to a mortar. After grinding for 20 minutes, pour it into a glass bottle and stir for 10 hours. Then pour the mixed slurry on the carbon felt, spread it evenly with a 200 μm scraper, and keep it at 80 ° C for 4 hours to obtain the ZnVO positive electrode.

[0038] Step 3, full battery assembly The zinc electrode and the zinc vanadate electrode are assembled into a CR2025 model (the battery has a diameter of 20.0 mm and a thickness of 1.6 mm) full battery. The assembly order of the entire battery is positive electrode shell, zinc vanadate positive electrode sheet, glass fiber diaphragm, zinc electrode, stainless steel gasket (thickness 1 mm), and negative electrode shell. The sealing pressure is about 50 kg per cubic centimeter. The battery needs to stand at room temperature for 2 hours before use. The diaphragm is glass fiber (produced by Whatman, with a diameter of 110 mm, cut into 19 mm discs for use). The electrolyte used is 2 mol / L (or 1M) zinc sulfate solution, 100 μL is added to each battery, and the electrolyte is added after the diaphragm is placed.

[0039] Step 4, zinc vanadate full battery test The full battery test uses the battery test system of Wuhan Blue Power. At room temperature (25°C), the charge and discharge test is carried out at a rate of 10C. Fig.12 As shown, the initial discharge capacity is 150 mAh g -1 , and then showed a downward trend, with the capacity dropping to 75 mAh g after about 1600 cycles. -1 . At -20℃, the charge and discharge test was carried out at 1C rate. Fig.13 As shown, the battery specific capacity decays rapidly.

[0040] Comparative Example 5 Assembling zinc vanadate full batteries using conventional hydrogel electrolytes Step 1, preparation of conventional hydrogel electrolyte membrane Same as step 1 of comparative example 1.

[0041] Step 2, zinc electrode preparation.

[0042] Same as step 1 of comparative example 2.

[0043] Step 3, preparation of zinc vanadate positive electrode Same as step 2 of comparative example 4.

[0044] Step 4, full battery assembly The zinc electrode and the zinc vanadate electrode are assembled into a CR2025 model (the battery has a diameter of 20.0 mm and a thickness of 1.6 mm) full battery. The assembly order of the entire battery is positive electrode shell, zinc vanadate positive electrode sheet, traditional hydrogel electrolyte, zinc electrode, stainless steel gasket (thickness 1 mm), negative electrode shell. The sealing pressure is about 50 kg per cubic centimeter. The battery needs to be left at room temperature for 2 hours before use.

[0045] Step 4, zinc vanadate full battery test The full battery test uses the battery test system of Wuhan Blue Power. At room temperature (25°C), the charge and discharge test is carried out at a rate of 10C. Fig.12 As shown, the initial discharge capacity is 150 mAh g -1 , then overcharged after about 900 cycles, causing the battery to short-circuit. At -20℃, the charge and discharge test was carried out at a rate of 1C. Fig.13 As shown in Figure 2, the battery capacity is only 120 mAh g after 400 cycles. -1 .

[0046] Example 1 Preparation of gel electrolyte (AM-CH3) by methyl solubilization and recrystallization strategy Step 1, methyl solubilization and recrystallization strategy First, the dissolution strategy of methyl cellulose, acrylamide, and zinc sulfate aqueous solution mixed in different proportions was studied. First, acrylamide and zinc sulfate were added to water in different proportions and stirred for 5 to 10 hours to study their solubility. The phase diagrams of different mixing proportions are shown in Figure 2. Figure 1 shown.

[0047] Step 2, Preparation of methyl-modified gel electrolyte First, 0.8 g acrylamide and 0.4 g methyl cellulose were dissolved in 10 mL 2 mol / L zinc sulfate aqueous solution and stirred for 6 hours to make them uniformly mixed; then 10 mg potassium persulfate and 5 mg N,N'-methylenebisacrylamide were added and stirred for 10 minutes; the mixed solution was placed on a double-layer glass plate and coated evenly and sealed to a coating thickness of 0.4 mm, and thermally polymerized in an oven at 60°C for 2 hours to obtain a methyl-modified hydrogel electrolyte, such as Figure 1 shown.

[0048] Step 3, Structural characterization of methyl-modified hydrogel electrolytes The surface morphology was observed using Zeiss dual ion beam scanning electron microscope (SEM). Figure 2 As shown in the figure, the surface of the methyl-modified hydrogel electrolyte is flat, with a small number of micropores and no large salt precipitation. At the same time, the ionic conductivity of the methyl-modified hydrogel electrolyte can reach 20.44 mS cm -1 , better than the comparative example, such as Figure 5 As shown, this is beneficial to the migration of zinc ions. XRD can prove that the methyl-modified hydrogel electrolyte has no obvious sharp peaks and exhibits an amorphous state, which indicates that the groups in the gel electrolyte interact with methyl cellulose and the electrolyte.

[0049] Example 2 Methyl-modified gel electrolytes for Zn-Zn symmetric batteries.

[0050] Step 1, Preparation of methyl-modified gel electrolyte Same as step 2 of Example 1.

[0051] Step 2, zinc electrode preparation Same as step 1 of comparative example 2.

[0052] Step 3, methyl-modified gel electrolyte assembly of Zn-Zn symmetric battery The zinc electrodes were assembled into a CR2025 model (battery diameter is 20.0mm, thickness is 2.5mm) symmetrical battery for cycle stability test. The battery components are the positive electrode shell, zinc electrode, methyl-modified hydrogel electrolyte membrane, zinc electrode, stainless steel gasket (diameter 16mm, thickness 1mm), negative electrode shell, and the sealing pressure is about 50 kg per cubic centimeter. The battery needs to be left at room temperature for at least 2 hours before use.

[0053] Step 4, methyl modified gel electrolyte assembly Zn-Zn symmetric battery test The methyl-modified gel electrolyte assembled zinc-zinc symmetric battery obtained in step 3 was subjected to cycle testing. The battery test system of Wuhan Blue Electric was used for battery testing. Fig. 9 As shown, the test parameters are set to constant current discharge and constant current charge, and the current density based on the electrode area is 1mA / cm 2 , area capacity is 0.5 mAh / cm 2 Under this test condition, the symmetrical battery life of the methyl-modified hydrogel electrolyte can reach more than 8000 hours, showing ultra-long cycle and excellent electrochemical performance. 2 , area capacity is 0.5 mAh / cm 2 Tests such as Fig.10 , 11As shown in Figure 2, the symmetrical battery life is approximately 2150 hours. In addition, under deep discharge conditions, such as Fig.11 As shown, at 0.5 mA / cm 2 、10mAh / cm 2 Under the same conditions (DOD=68.33%), the symmetrical battery can still achieve 2600 hours.

[0054] Step 5: Comparison of test results with the zinc symmetric battery in the comparative example Methyl-modified hydrogel electrolyte for symmetric Zn-Zn battery assembly at 1 mA / cm 2 、0.5mAh / cm 2 and 0.5mA / cm 2 、10mAh / cm 2 The test results under test conditions are as follows Fig.11 , the battery life reaches 8000 hours and 2600 hours respectively, far exceeding the control ratio. This fully demonstrates that the methyl-modified gel electrolyte can significantly improve battery performance and greatly increase cycle life.

[0055] Step 6: Use SEM to observe the surface morphology of the zinc electrode after long-term cycling After the cycle test of the zinc-zinc symmetric battery assembled with methyl-modified gel electrolyte, the surface morphology of the zinc electrode is as follows Figure 6 As shown in the figure, it can be seen that the zinc surface presents dense deposition, no obvious dendrites, and the surface is flat. Compared with the use of hydrophilic glass fiber separator, the zinc deposition is obviously more flat and orderly, which shows that the gel electrolyte can regulate the dense deposition of zinc.

[0056] Step 7: Elucidate the mechanism of action of methyl-modified gel electrolyte in zinc batteries In order to improve the solubility of gel electrolyte and reduce the free water activity to inhibit its salting out, the ternary solubilization equilibrium process of AM (or AM-CH3), ZnSO4 and H2O was studied, such as Figure 3 As shown in Figure 2, the solubility of mixtures with different proportions varies greatly. Figure 4 As shown in the figure, the dissolution process of gel electrolyte was studied, and it was found that in a solution containing methyl cellulose, its solubility can be significantly improved to prevent electrolyte salting out. This solubilization strategy is based on the methyl modification method, which converts the protic polymer acrylamide into a non-protic polymer and weakens the intermolecular hydrogen bonds. The unoccupied -C=O site in acrylamide participates in the Zn 2+ Solvation, thereby increasing the electrolyte salt concentration. In the process of preparing gel electrolytes by thermal polymerization, this solubilization and recrystallization strategy retains a small amount of bound water and promotes the crystallization of the electrolyte.

[0057] Figure 8To study the stability of the electrode interface at room temperature, the methyl-modified hydrogel electrolyte reduces the activity of a large amount of free water and retains only a small amount of bound water, which reduces the corrosion reaction at the electrode interface and increases the stability of the electrode-electrolyte interface. At the same time, methylcellulose has an affinity for zinc, which regulates the solvation structure of zinc ions in the electrolyte and induces uniform deposition of zinc ions, such as Figure 7 shown.

[0058] Example 3 Methyl-modified gel electrolyte for zinc vanadate full batteries.

[0059] Step 1, Preparation of methyl-modified gel electrolyte Same as step 2 of Example 1.

[0060] Step 2, zinc electrode preparation Same as step 1 of comparative example 2.

[0061] Step 3, preparation of zinc vanadate positive electrode Same as step 2 of comparative example 4.

[0062] Step 4: Assembly of zinc vanadate full battery with methyl-modified gel electrolyte The zinc electrode and the zinc vanadate electrode are assembled into a CR2025 model (the battery has a diameter of 20.0 mm and a thickness of 1.6 mm) full battery. The assembly order of the entire battery is the positive electrode shell, the zinc vanadate positive electrode sheet, the methyl-modified hydrogel electrolyte, the zinc electrode, the stainless steel gasket (thickness 1 mm), and the negative electrode shell. The sealing pressure is about 50 kg per cubic centimeter. The battery needs to be left at room temperature for 2 hours before use.

[0063] Step 5: Methyl-modified gel electrolyte assembly of zinc vanadate full battery test The full battery test uses the battery test system of Wuhan Blue Power. At room temperature (25°C), the charge and discharge test is carried out at a rate of 10C. Fig.12 As shown, the initial discharge capacity is 120 mAh g -1 After about 1600 cycles, the specific capacity remained at 110 mAh g -1 At -20℃, the charge and discharge test was carried out at 1C rate. Fig.13 As shown, the battery specific capacity hardly decays after 400 cycles, and the capacity retention rate is 98.46%.

[0064] Step 6: Compare the performance of the zinc vanadate full battery with that of the comparative example The zinc vanadate battery assembled with glass fiber separator has a rapid capacity decay under 10C rate charge and discharge conditions, making it difficult to use in practice; the zinc vanadate battery assembled with traditional hydrogel electrolyte is prone to overcharge, short circuit and other faults under 10C rate charge and discharge conditions, which is mainly related to interface instability; the zinc vanadate battery assembled with methyl-modified hydrogel electrolyte has excellent specific capacity after 1600 cycles under 10C rate charge and discharge conditions, and has excellent electrochemical performance. In addition, methyl-modified gel electrolytes are still widely used in low-temperature environments. The assembled zinc vanadate battery has almost no capacity decay after 400 cycles, which has great application value in low-temperature flexible battery scenarios.

[0065] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. The present disclosure is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the claims.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. The patent protection scope of the present invention shall be based on the claims. All equivalent structural changes made using the contents of the specification of the present invention should also be included in the protection scope of the present invention.

Claims

1. A method for preparing a methyl-modified hydrogel electrolyte, characterized in that: The process is as follows: 1) Dissolve acrylamide and methyl cellulose in a zinc sulfate aqueous solution at a mass ratio of (1-3):1 and stir for 5-10 hours to mix them evenly; 2) Add thermal initiator and crosslinking agent to the mixed solution of step 1) and stir for 5 to 10 minutes; 3) The mixed solution of step 2) is placed in a double-layer substrate, coated evenly and sealed, and thermally polymerized at 50-70° C. to obtain a methyl-modified hydrogel electrolyte.

2. The method for preparing a methyl-modified hydrogel electrolyte according to claim 1, characterized in that: The thermal initiator is potassium persulfate or ammonium persulfate, and the crosslinking agent is N,N'-methylenebisacrylamide; the amount of the thermal initiator added is 1-5% of the mass of acrylamide; the mass ratio of the thermal initiator to the crosslinking agent is (1-3):

1.

3. The method for preparing a methyl-modified hydrogel electrolyte according to claim 1, characterized in that: The spacing between the double-layer substrates is 0.1~1 mm, and the thermal polymerization time is 2~4 hours.

4. The method for preparing a methyl-modified hydrogel electrolyte according to claim 1, characterized in that: The concentration of the zinc sulfate aqueous solution is 1~5 mol / L, and the concentration of acrylamide in the acrylamide is 0.05~0.1 mg / mL.

5. A methyl-modified hydrogel electrolyte prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the methyl-modified hydrogel electrolyte according to claim 5 in zinc batteries.

7. The use according to claim 6, characterized in that: The zinc sheet is used as the negative electrode, the zinc sheet or zinc vanadate positive electrode is used as the positive electrode, and the prepared methyl-modified hydrogel electrolyte is used as the battery separator and electrolyte to be assembled into a zinc-zinc symmetric battery or a zinc-vanadate full battery.

8. The use according to claim 6, characterized in that: The structure of the zinc-zinc symmetrical battery is: positive electrode shell, zinc sheet, methyl-modified gel electrolyte, zinc sheet, gasket, and negative electrode shell; the structure of the zinc-zinc vanadate full battery is: positive electrode shell, zinc vanadate positive electrode, methyl-modified gel electrolyte, zinc sheet, gasket, and negative electrode shell.

9. The use according to claim 7 or 8, characterized in that: The preparation process of the zinc vanadate positive electrode is as follows: vanadium pentoxide is dispersed in a mixture of water and acetone, zinc acetate is added and stirred to dissolve, and then the mixture is transferred to a sealed polytetrafluoroethylene container, kept at 200±10°C for 70 to 75 hours, and water is added for centrifugal washing. The solid is collected and dried to obtain zinc vanadate, PVDF is added to NMP and stirred until completely dissolved, zinc vanadate and acetylene black are ground and poured into the NMP solution of PVDF and stirred for 10 to 15 hours, and then the mixture is applied to the current collector with a scraper and dried to obtain the zinc vanadate positive electrode.

10. The use according to claim 9, characterized in that: The molar ratio of vanadium pentoxide to zinc acetate is 2:(1-1.5), the volume ratio of water to acetone is (10-20):1, and the mass ratio of zinc vanadate powder, acetylene black and PVDF is (6-8):(1-3):1.

Citation Information

Patent Citations

  • Compressible rechargeable zinc-manganese battery and battery-sensor integrated device based on battery

    CN109687040A

  • Double-network gel electrolyte for zinc ion battery as well as preparation method and application of double-network gel electrolyte

    CN117567771A

  • Gel-based flexible zinc-air battery suitable for low-temperature environment

    CN118507935A

Cited By

  • Preparation method of organic eutectic gel electrolyte and zinc metal battery

    CN120966025A